Ligand-free one-pot synthesis of Ru/W18O49 self-assembled hierarchical coral-like nanostructures for selective conversion of glucose into glycols - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Kirali, Arun Arunima Balachandran; Marimuthu, Banu; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2023)
In this study, we report a simple inorganic route for the synthesis of Ru/W18O49 self-assembled coral-like nanostructures, with the following advantages: It is one step and requires no surfactant or stabilizing agent; Ru loading is easily tuned, and the as-synthesized nanomaterials can be used as a catalyst without any further processing. The preliminary investigations of the catalytic performance of these as-synthesized Ru/W18O49 nanomaterials appear quite promising for converting glucose to glycols. The total glycol selectivity of 82.6% with 100% conversion of glucose was obtained over 0.03 wt % Ru loading on tungsten nanostructures, which turns out to be the lowest Ru loading% on support reported to date to achieve the highest total glycol selectivity among the previously reported catalyst based on Ru-nano/composite materials. Additionally, preliminary results show that the concentration of Ru on W18O49 significantly affects the selectivity of the glycol production. Thus, our methodology will open up a wide range of opportunities regarding the choice of metals, stoichiometric/nonstoichiometric WOx (x=1-3) as support, and the viability of further catalytic manipulations. A probable catalytic mechanism for this catalytic process is also proposed.
Keywords: glycols; Nanostructure; One-pot synthesis; ruthenium (Ru); selective conversion of glucose; tungsten oxide (W18O49)